Pelaksanaan Program Children Educational Support Dalam Mengurangi Prevalensi Anak Jalanan Oleh Yayasan Indonesian Street Children Organisation (ISCO) : Studi Deskriptif Di Sanggar (ISCO) Kelurahan Kebun Melati, Tanah Abang - Amalia, Wirda; Sekar, Dwi Amalia Chandra (Jurnal Ilmu Kesejahteraan Sosial, 2014)
This article discusses about the implementation of children educational support in reducing prevelance of street children by ISCO Foundation. Motivated by many poor children vulnerable to be street cause the difficulty of access to educational services. This research used a qualitative approach. Collecting data using observation and interview with 9 informant. The study results show that implementation of program has already ran fairly well characterized by reduced child beneficieris who took the streets due to provision of assistance in formal and non-formal education. This made the fulfillment of poor children needs to get an education from early age so the intensity of street work has minimized.